2004
DOI: 10.1161/01.atv.0000118683.99628.42
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Dystrophin in Mice Reduces NO-Dependent Vascular Function and Vascular Density: Total Recovery After a Treatment with the Aminoglycoside Gentamicin

Abstract: Objectives-Mutations in the dystrophin gene causing Duchenne's muscular dystrophy (DMD) lead to premature stop codons. In mice lacking dystrophin (mdx mice), a model for DMD, these mutations can be suppressed by aminoglycosides such as gentamicin. Dystrophin plays a role in flow (shear stress)-mediated endothelium-dependent dilation (FMD) in arteries. We investigated the effect of gentamicin on vascular contractile and dilatory functions, vascular structure, and density in mdx mice. Methods and Results-Isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 41 publications
6
83
1
3
Order By: Relevance
“…Normalization of NO production attenuated skeletal muscle damage and inflammation without affecting angiogenesis. 34 Recently, Loufrani et al 35 demonstrated that endothelium-dependent vascular smooth muscle relaxation was altered in mdx mice, resulting in attenuation of flow-induced vasodilation. Moreover, the same authors showed that vessel density was decreased in gracilis muscle of mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of NO production attenuated skeletal muscle damage and inflammation without affecting angiogenesis. 34 Recently, Loufrani et al 35 demonstrated that endothelium-dependent vascular smooth muscle relaxation was altered in mdx mice, resulting in attenuation of flow-induced vasodilation. Moreover, the same authors showed that vessel density was decreased in gracilis muscle of mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…In mdx mice treated with gentamycin for 2 weeks FMD was equivalent to control 44 . Related compounds with a higher efficiency and less toxicity are actually studied in order to find a treatment of some forms of myopathy 45 .…”
Section: -Mechanotransduction Of Shear Stress: Role Of the Structurementioning
confidence: 99%
“…Indeed, desmin is most likely involved in the contractility of smooth and skeletal muscle. Defects in the gene encoding for desmin induce rare but severe cardiomyopathies 44 .…”
Section: -Mechanotransduction Of Shear Stress: Role Of the Structurementioning
confidence: 99%
“…Arteries were bathed in a physiological salt solution maintained at 37 1C, pH 7.4 (pO 2 160 mm Hg, pCO 2 37 mm Hg). 30 Wall tension was applied as previously described. 31 In brief, arteries were set to the baseline circumference L 0 , where L 0 ¼0.9L 100 is the internal circumference that the artery would have in vivo when relaxed and under a transmural pressure of 100 mm Hg.…”
Section: Isolated Mesenteric Arterymentioning
confidence: 99%